2012
DOI: 10.1002/jor.22121
|View full text |Cite
|
Sign up to set email alerts
|

Is double inactivation of the Nf1 gene responsible for the development of congenital pseudarthrosis of the tibia associated with NF1?

Abstract: The pathogenic mechanism responsible for congenital pseudarthrosis of the tibia (CPT) is not well understood although the possibility of double inactivation of the neurofibromatosis type 1 (Nf1) gene has been suggested. In the present study, loss of heterozygosity was investigated in fibrous hamartoma tissues harvested from 16 patients with CPT associated with NF1 using four genetic markers that span the Nf1 gene. Based on the assumption that a single cell with double inactivation of Nf1 would undergo clonal g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 30 publications
2
23
0
Order By: Relevance
“…Osteoclastogenesis can be activated by RAS signaling, such as occurs in Nf1 deficiency (5,11,(41)(42)(43)(44)(45)(46)(47)(48)(49)(50). We observed a gain in the number of osteoclasts at the Nf1-null murine fracture site, in agreement with previous studies (51)(52)(53)(54)(55)(56)(57).…”
Section: Discussionsupporting
confidence: 91%
“…Osteoclastogenesis can be activated by RAS signaling, such as occurs in Nf1 deficiency (5,11,(41)(42)(43)(44)(45)(46)(47)(48)(49)(50). We observed a gain in the number of osteoclasts at the Nf1-null murine fracture site, in agreement with previous studies (51)(52)(53)(54)(55)(56)(57).…”
Section: Discussionsupporting
confidence: 91%
“…All samples were collected from individuals after obtaining written informed consent approved by the Institutional Review Board of the University of Texas Southwestern Medical Center, the University of Utah, or Seoul National University Hospital. Five of the 16 samples included in this study were reported previously with inconsistent results after genotyping four polymorphic markers (D17S1863, GXALU, IN38, and 3 NF1 ‐1) near the NF1 locus . In this study, no sample showed evidence of LOH across all markers in the pseudoarthrosis compared to matched blood/saliva, and this method is unable to distinguish copy‐neutral LOH from LOH caused by somatic gene deletion.…”
Section: Methodsmentioning
confidence: 76%
“…Long‐bone dysplasia and pseudoarthrosis were previously proposed to result from localized biallelic inactivation of NF1 owing to somatic LOH . However, subsequent studies reported inconsistent or inconclusive results in additional patients, and the genomewide spectrum of somatic mutations in pseudoarthrosis tissue was never investigated …”
Section: Introductionmentioning
confidence: 99%
“…Animal studies have provided a definitive link between Nf1 2/2 progenitor cells and a fibrous nonunion, but the precise role of Nf1 2/2 cells in fibrosis is still unresolved 18,33 . Biopsies from fractures have identified loss of heterozygosity in NF1 fractures, but exceptions have been reported 13,34,35 . Cultures of the pseudarthrosis tissue expressed high levels of the proosteoclastic cytokine RANKL, in parallel with clinical findings 13,36 .…”
Section: Discussionmentioning
confidence: 99%